(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The activity of the first Hercynian tectonic phase is documented in the Lake Mulargia area (central Sardinia) by the presence of numerous tectonic units. We have examined in particular the southern region of the lake, where one of the upper tectonic units (the Bruncu Maresusus Unit) outcrops. It has at its base a thick silicoclastic succession where we have found Tremadocian Acritarchs in its stratigraphically upper part. This formation is time—equivalent to the Solanas Formation and the Arenarie di San Vito Auct. Another tectonic unit, Bruncu Brevexilis, constitu ted from bottom to top of metavolcanities of probable middle Ordovician age and fossiliferous sediments of Caradocian, Silurian and Devonian age, is also present in the same area and lies under the Bruncu Maresusus Unit.